MENYIBAK LAPISAN MAJĀZ ‘AQLĪY: KAJIAN TEORETIS DAN PEMBAGIANNYA - Suci Nur Fadillah Yunus; Muhammad Harjum; M. Fatkhul Ulum (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The Arabic language possesses rich meanings and structures that allow the conveyance of messages both literally and figuratively. One important aspect in the study of balāghah is majāz ‘aqlī, which refers to the attribution of an action to a party that is not the actual doer, and can be understood through reason and logical consideration. This study aims to describe the definition, elements, and classification of majāz ‘aqlī, as well as its application in the Qur’anic text. The research employs a qualitative descriptive approach based on library research, with data sources including classical balāghah texts and relevant journal articles. The results show that majāz ‘aqlī consists of four main elements: musnad, musnad ilayh, ‘alāqah, and qarīnah, and can be classified into several types based on the pattern of attribution, such as zamāniyyah (time), makāniyyah (place), sababiyyah (cause), al-maṣdariyyah (verbal noun), al-maf‘ūliyyah (object noun), and al-fā‘iliyyah (subject noun). Understanding majāz ‘aqlī enables readers to distinguish between literal and figurative meanings, comprehend implicit messages, and interpret Qur’anic verses accurately. This study contributes to enriching contemporary Arabic balāghah studies, particularly in stylistic expression and attribution of meaning, and supports the development of Arabic linguistic studies in Indonesia.